NAVIGATING THE FUTURE: UNDERSTANDING THE ESSENTIAL COMPONENTS FOR SUCCESSFUL SMART PARKING SOLUTIONS - AL ABUDY, ISRAA M.; EL ABBADI , NIDHAL K. (Journal of Duhok University, 2023)
In an era when there is increasing talk about the rapid growth in technology, it has become necessary to advance the service requirements of our daily lives, and the first thing we face is traffic jams and time spent searching for safe parking spaces. The smart parking system is a promising solution to face many of the problems that accompany large cities, where lack of work is considered one of the factors that cause pollution and the difficulty of movement due to congestion, which has become one of the main obstacles facing the community. The common way to find a parking space is the traditional way as the driver usually finds a place in the city through his periodic experience, searching, or luck. This process requires time and effort and may result in the worst-case scenario if the driver is driving in a city with high traffic especially at peak hours. Smart parking solutions are characterized by a specific architecture (such as cameras, sensors, communication protocols, and software solutions). But despite the limitations of these components, they constitute a smart parking solution. This paper discusses the most used types of components which guides the commuters to decide on the selection of component types to implement a smart parking solution.